Myeloid Neoplasms in the Guise of Nutritional Deficiency - Veda Parthasarathy (Case Reports in Hematology)
The classic BCR-ABL-negative myeloproliferative neoplasms (MPNs) which include polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) are among the most frequent hematologic neoplasms. Because of their relatively smooth clinical course, it is likely that many of these MPNs actually go undetected. Considering the high prevalence of iron, folic-acid, and vitamin B12 deficiencies in developing countries, their coexistence with MPN can be expected frequently. In such situations where both disorders coexist, MPN is often overlooked. This causes considerable diagnostic delay. In this paper, two cases of PMF and one case of PV where the diagnosis of MPN was delayed for about 3 years are discussed. Presence of concomitant vitamin B12, folate, and iron deficiencies perhaps camouflaged the underlying MPN. Bearing in mind the possibility of MPN, even in the setting of apparent nutritional deficiency and performing a bone marrow evaluation, is the crucial step in unveiling the hidden MPN.